The most frequent phytonyms in - Ould Mohamed Baba, Ahmed-Salem (Anaquel de Estudios Árabes, 2006)
This paper contains the most frequent names of plants, bushes and trees in the Hassāniyyä dialect; provides their botanical identification, some of their characteristics and their alphabetical repertoire.